Kinerja dan Proyeksi Pelayanan Kapal di Dermaga 004 Pelabuhan Banten - Shindy Claudia Simamora (Fakultas Teknik Transportasi dan Logistik Trisakti, 2023)
This research was conducted at pier 004 of Port of Banten to analyze the performance of ship services and liquid bulk cargo, with 31% fuel and 69% non-fuel. The results of the analysis are compared with operational performance standards, that the performance of pier 004 was waiting time value good of 0.42 below standard 1 hour, approach time value good of 0.87 below standard 1 hour, good of ET:BT ratio 69.2% below standard 80%, and BOR value with 1 mooring good of 50% below standard 70%. Overall the service performance of pier 004 is good. The results of the analysis of the projections for the next 10 years, the current cargo load in 2022 is 509,289 tons/m3 and in 2032 it will reach 603,618 tons/m3, the ship call will increase by 8 tankers every year and in 2032 it will reach 278 ships, with an LOA classification of 164 m, with a maximum DWT of 50,000. Therefore the capacity of the pier must be anticipated to be developed, including adding 2 units mooring dolphin dimensions of length 9.6 m x 10 m, dredging pond of pier -3.90 m, replacement type fender cell and cone with specifications SCK 14500/SCN 1100 or CSS 1450 H/SPC 1100 H.